Physico‐Chemical Processes. (1st October 2015) - Hua, Bin; Xiong, Huixin; Wang, Zhengyang; Hill, Jonathan; Buckler, Samuel; Gao, Shuang; Yang, John; Deng, Baolin
Abstract : This review is on the research literature published in 2014 related to the physico‐chemical processes for water and wastewater treatment. The review is divided into six sections, including coagulation/flocculation, filtration, sedimentation, oxidation, flotation, sorption process.